(untitled) (Bangladesh Journal of Botany, 2018)
Assessment of plant growth promoter and biocontrol properties of plant growth promoting rhizomicroorganisms (PGPR) from tea soil against black rot disease agent of tea caused by Corticium theae Bernard in Bangladesh was done. The antagonistic microorganisms were isolated from rhizosphere soils of tea fields and cultured on different nutrient media. The isolates were screened for their antagonism against Corticium theae by dual culture technique. The microbial strains were inoculated with tea nursery soils by mixing with 50 g of decomposed cowdung. In tea plantations, the microbial strains were sprayed on diseased plants two times at 15 days intervals. Four different species of PGPR strains such as Bacillus, Pseudomonas, Streptomyces, Trichoderma were isolated from rhizospheric soil of tea. These PGPR strains enhanced plant growth in nursery and had a positive effect on the rate of increased in number of leaves, height of plants and girth of plants by 33, 43 and 3%, respectively. Lowest severity of black rot was found in plants treated with Trichoderma followed by Bacillus, Pseudomonas and Streptomyces strains. Trichoderma and Bacillus caused 16 and 14% reduction of disease severity while both Pseudomonas and Streptomyces strains reduced disease severity by 10%. All the PGPR’s have a great influence in reducing disease severity by 19% with optimistic relations. Radial mycelial growth of C. theae was also inhibited in similar trends. The biofertilizer showed comparatively lower response in reducing disease severity (8%) in comparison to PGPR’s. It can be concluded that Bacillus, Pseudomonas, Streptomyces and Trichoderma isolated from tea soil have their growth enhance capacity as well as decrease the disease severity of black rot in tea.